School Administration and Its Effects on Teaching Quality of Secondary School Teachers in Luang Prabang Province - Deelivong, Somphone; Keoboualapheth, Soulideth; khotsaigno, Saiphone; Phanthachit, Somchit; Vandalak, Phonesavanh (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
The objectives of this research were: 1) to study school administration in secondary schools in Luang Prabang Province; 2) to study the teaching performance of secondary school teachers; and 3) to investigate the impact of school administration on teaching performance. This study employed a survey research design, using questionnaires to collect data from a sample of 89 secondary school teachers in Luang Prabang Province. Data were analyzed using mean (bar(x)) standard deviation (S.D.), and Multiple Regression Analysis via the SPSS program. The research findings revealed that: School administration in secondary schools in Luang Prabang Province was overall at a good level. Specifically, the highest-rated aspect was the assignment of duties and responsibilities appropriate to teachers' knowledge and abilities, followed by a positive working atmosphere, and the recognition and appreciation of work performance. Teaching performance of the teachers was overall at a very good level. The highest-rated aspect was the classroom environment facilitating teaching, followed by continuous training and skills development, and the support for using technology in teaching and learning. The impact of administration on teaching: Factors including a positive working atmosphere, clear communication between administrators and teachers, and regular recognition based on actual work performance significantly influenced teaching performance at a 0.05 level of significance. These administrative factors collectively explained 70.0% (R2= 0.70) of the variance in teachers' teaching performance.